f ( x) = 2 x 2 + 3 x - x 4 - 7 x 2 + 3 x - 1<br />
x = 3+ 2<br />
x = 3+ 2<br />
f (3 + 2) » 36, 22815<br />
<br />
f ( x) =<br />
<br />
x 2 - 3x + 1<br />
sin x + cos x - 2<br />
<br />
y = -2 x -<br />
<br />
1<br />
4<br />
<br />
y=<br />
<br />
x3 x 2<br />
1<br />
+ - 2x 3 2<br />
3<br />
<br />
ì x1 = -0,5 ì x2 » 0,36603 ì x3 » -1,36603<br />
í<br />
í<br />
í<br />
î y1 = 0, 75 î y2 » -0,98205 î y3 » 2, 48205<br />
<br />
5<br />
5<br />
21<br />
1<br />
a = ,b = ,c =- ,d = ;<br />
4<br />
6<br />
4<br />
6<br />
<br />
ÑEÀ THI NAÊM 2001<br />
<br />
ì x1 » 1,8633 ì x2 » 0,5367<br />
í<br />
í<br />
î y1 » 0, 7266 î y2 » -1,9266<br />
<br />
ì x1 » 0, 4641 ì x2 » 0, 4641<br />
í<br />
í<br />
î y1 » 1,3625 î y2 » -1,3625<br />
<br />
f ( x ) = cos 2 x - 2 cos x<br />
<br />
x2 y2<br />
+<br />
=1<br />
16 9<br />
<br />
3x - y - 1 = 0<br />
ì x1 » 1, 2807 ì x2 » -0, 6532<br />
í<br />
í<br />
î y1 » 2,8421 î y2 » -2,9597<br />
<br />
ì x1 » 1, 7735<br />
ì x2 » -1,9735<br />
í<br />
í<br />
î y1 » -0,9245 î y2 » 0,3245<br />
<br />